Nitrogen addition enhances nitrogen but not carbon mineralization in aggregate size fractions of soils in a Pinus massonia plantation - Chen, Tian; Cheng, Ruimei; Xiao, Wenfa; Zeng, Lixiong; Shen, Yafei; Wang, Lijun; Sun, Pengfei; Zhang, Meng; Li, Jing (Frontiers in Forests and Global Change, 2024)
Atmospheric nitrogen (N) deposition can impact the levels of soil organic carbon (SOC) and total nitrogen (total N) by altering the soil N availability. However, the effect of N input on the mineralization of SOC and total N in various soil aggregate size fractions requires further clarification. The study utilized soil samples collected from a Pinus massoniana plantation situated in the Three Gorges Reservoir Area of China. Over a period of three years, the soils from the plantation were subjected to four different levels of nitrogen addition (0 [N0], 30 [N30], 60 [N60], and 90 [N90] kg N ha -1 yr -1 ). The impact of N addition on the mineralization of SOC and total N in aggregates was evaluated through an incubation experiment, encompassing four aggregate sizes (2000 -8000, 1000 -2000, 250 -1000, and < 250 μm). These analyses revealed that the < 250 μm fraction showed the highest levels of cumulative C mineralization, while the lowest levels were observed in the 2000 -8000 μm fraction. Compared to the < 250 um fraction, a drop of 9 -21% in cumulative C mineralization was observed in the 2000 -8000 μm fraction, indicating that soil aggregates enhance the stability of C in the soil. Cumulative N mineralization levels were consistently at their lowest in the 2000 -8000 μm fraction, indicating aggregates reducing mineralization-related N loss. Adding N to forest soil samples led to a reduction in cumulative C mineralization. In contrast, an opposite trend was observed in the cumulative N mineralization after adding N in microaggregates. Nitrification was the main contributor to net N mineralization. SOC and total levels increased in response to N30 and N60. N addition leads to an increase in the weight ratio of the 1000 -2000 μm fraction.Moreover, N90 was linked to decreases in microbial biomass C and N. In conclusion, these findings confirm that the structural characteristics of soil aggregates play a crucial role in sequestering organic carbon and total N sequestration in the presence of N deposition, while highlighting N loss from the soil caused by N input.